Characterizing superficial cerebral cortical venous anatomy for endovascular device implantation: a cross- sectional imaging study. - Brannigan, Jamie; Kian, Azadeh; Eiber, Calvin; Tarigoppula, Venkata S. Aditya; Bogard, Jillian; Siddiqui, Adnan H.; Rind, Gil; Berenstein, Alejandro; Majidi, Shahram; Oxley, Thomas J. (Journal of NeuroInterventional Surgery, 2026)
Background Neurovascular electronic devices, including brain- computer interfaces (BCIs), offer a minimally invasive approach to diagnosing and treating neurological disorders. Implanting BCIs in superficial cortical veins, owing to their proximity to sensorimotor cortices, may improve motor function restoration. However, marked anatomical variability and the complex anteriorly directed connection with the superior sagittal sinus (SSS) complicate device navigation. This exploratory study aimed to characterize cortical venous anatomy to inform device design and procedural planning. Methods Retrospective imaging data from 25 patients were analyzed using magnetic resonance venography (MRV) and computed tomography venography (CTV). Vessel segmentation and analysis quantified parameters such as vein presence, diameter, length, angulation, and tortuosity. In 12 patients, T1- weighted magnetic resonance imaging (MRI) was used to extract cortical gyri and sulci, assessing vessel--cortex relationships. Results The superior anastomotic vein (vein of Trolard) was identified bilaterally in 84% of patients, with a mean entrance diameter of 4.4 mm. Frequent transient constrictions (<2 mm) were reported. The precentral vein was present bilaterally in 52% of cases. Most cortical veins exhibited take- off angles >90 degrees from the SSS, presenting challenges for endovascular navigation, with overall considerable anatomical variability observed. Conclusion The vein of Trolard shows promise as a target for endovascular BCIs given its consistent presence and favorable dimensions. Nonetheless, constrictions and steep angulation at the SSS confluence pose challenges for device deployment. A new framework is necessary for the classification of cortical venous anatomy, to guide patient selection and procedural planning, which will require further development and validation.